2011
DOI: 10.1007/s11434-011-4866-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of soil stoichiometry of the CaCO3/available phosphorus ratio on plant density in Artemisia ordosica communities

Abstract: In soil, CaCO 3 can reduce the availability of phosphorus in arid and semi-arid regions, thereby influencing plant growth. However, the effects of soil stoichiometry of the CaCO 3 /available phosphorus ratio (CaCO 3 /AP ratio) on plant density are unknown. In this study, we examined 4 Artemisia ordosica communities located in arid and semi-arid regions, and performed a pot experiment with an orthogonal design to examine the relationships between the soil CaCO 3 /AP ratio and plant density. The results showed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…Two other dominant species of dune slope were of the Artermisia genus. Plants of Artermisia genus showed increased growth and density in arid sandy desert with an increase in soil phosphorus (Zhao et al, 2012). Our study also showed a positive correlation of A. songorica and A. xerophytica with soil phosphorus in the 20cm depth (axis 2, Figure 4).…”
Section: Discussionsupporting
confidence: 66%
“…Two other dominant species of dune slope were of the Artermisia genus. Plants of Artermisia genus showed increased growth and density in arid sandy desert with an increase in soil phosphorus (Zhao et al, 2012). Our study also showed a positive correlation of A. songorica and A. xerophytica with soil phosphorus in the 20cm depth (axis 2, Figure 4).…”
Section: Discussionsupporting
confidence: 66%
“…In addition, high concentrations of iron (Fe) and aluminum (Al) in red soils will reduce the availability of P through the synthesis of Fe-P and Al-P [61,62]. Furthermore, karst ecosystems have an abundance of CaCO 3 , which results in relatively low P bioavailability [63].…”
Section: Nutrient Limitationmentioning
confidence: 99%
“…Therefore, the study on the A. ordosica shrub species is important for understanding the progress of vegetation restoration in this study area. Recent research on A. ordosica population dynamics mostly concentrated on natural recruitment [ 15 , 47 ], effects of habitat changes [ 15 , 48 , 49 ], spatial pattern [ 50 , 51 ], plant morphology and structural characteristics [ 52 ], soil moisture characteristics [ 53 , 54 ], and soil physicochemical properties [ 55 ]. However, the dynamics of the population structure and spatial pattern of the A. ordosica population in a restored desert grassland after removing livestock have not received enough attention.…”
Section: Introductionmentioning
confidence: 99%